Watershed Regressions for Pesticides (WARP) Models for Predicting Stream Concentrations of Multiple Pesticides. Issue 6 (1st November 2013) - Stone, Wesley W.; Crawford, Charles G.; Gilliom, Robert J.
Abstract : Watershed Regressions for Pesticides for multiple pesticides (WARP‐MP) are statistical models developed to predict concentration statistics for a wide range of pesticides in unmonitored streams. The WARP‐MP models use the national atrazine WARP models in conjunction with an adjustment factor for each additional pesticide. The WARP‐MP models perform best for pesticides with application timing and methods similar to those used with atrazine. For other pesticides, WARP‐MP models tend to overpredict concentration statistics for the model development sites. For WARP and WARP‐MP, the less‐than‐ideal sampling frequency for the model development sites leads to underestimation of the shorter‐duration concentration; hence, the WARP models tend to underpredict 4‐ and 21‐d maximum moving‐average concentrations, with median errors ranging from 9 to 38% As a result of this sampling bias, pesticides that performed well with the model development sites are expected to have predictions that are biased low for these shorter‐duration concentration statistics. The overprediction by WARP‐MP apparent for some of the pesticides is variably offset by underestimation of the model development concentration statistics. Of the 112 pesticides used in the WARP‐MP application to stream segments nationwide, 25 were predicted to have concentration statistics with a 50% or greater probability of exceeding one or more aquatic life benchmarks in one or more stream segments. Geographically, many of the modeled streams in the Corn Belt Region were predicted to have one or more pesticides that exceeded an aquatic life benchmark during 2009, indicating the potential vulnerability of streams in this region.